Dental re-implantation 72 hours after avulsion - Alain Manuel Chaple Gil; Yamilé Baganet Cobas (Editorial Ciencias Médicas, 2014)
The dental re-implantation is one of the procedures demanding most rigor and precision in terms of the conditions required to achieve the expected success. Our purpose is to present the evolution and treatment of a case of auto-implantation of the upper left lateral incisor 72 hours after avulsion. The patient was a male 18 year-old with a history of ill health presents three days after avulsion of the upper left lateral incisor as a result of trauma. The patient was informed of the possible failure of the treatment due to the time elapsed. In cases such as this one, immediate treatment is essential to achieve success. Dental re-implantation and ferulization were performed. The tooth was treated endodontically on two visits one week apart. Checkups were conducted which were quarterly at first and then biannual. Almost five years later, radiographic evidence shows no complications and clinical appearance is normal. The results were satisfactory. The patient has preserved his tooth for five years and his status is totally asymptomatic.